CellPAINT: Turnkey Illustration of Molecular Cell Biology - Gardner, Adam; Autin, Ludovic; Fuentes, Daniel; Maritan, Martina; Barad, Benjamin A.; Medina, Michaela; Olson, Arthur J.; Grotjahn, Danielle A.; Goodsell, David S. (Frontiers in Bioinformatics, 2021)
CellPAINT is an interactive digital tool that allows non-expert users to create illustrations of the molecular structure of cells and viruses. We present a new release with several key enhancements, including the ability to generate custom ingredients from structure information in the Protein Data Bank, and interaction, grouping, and locking functions that streamline the creation of assemblies and illustration of large, complex scenes. An example of CellPAINT as a tool for hypothesis generation in the interpretation of cryoelectron tomograms is presented. CellPAINT is freely available at http://ccsb.scripps.edu/cellpaint.